Synthesis of Carbon thin films using Aerosol-Assisted Chemical Vapour Deposition (AACVD) - Al-Dulaimi, Naktal (Sulaimani Journal for Pure and Applied Sciences, 2022)
Aerosol-assisted chemical vapour deposition (AACVD) technique was used to produce carbon thin films. The synthesised films have been deposited using chloroform solvent as a single source precursor at 550 °C. Raman spectroscopy, powder X-Ray diffraction (p.XRD), and scanning electron microscope (SEM) were used to characterize the thin films and the result shows that carbon thin films successfully have been prepared. Carbon thin films were produced from chloroform solvent as a single source precursor therefore, this work recommends to avoid using chloroform as a solvent in AACVD technique when the deposition carried out at high temperatures (above 500 ºC), to keep the deposited materials pure from high level of carbon contamination.
Keywords: Carbon thin films; AACVD; 2D Materials; Amorphous Carbon